The Role of Universities in Curbing Interregional Educational Migration - I. V. Zakharova (Высшее образование в России)
The article addresses the problem of outflow of youth from the region in connection with higher education. The aim is to determine the possibility of influencing the flows of interregional educational migration. The role of universities in curbing educational migration from the region and in attracting migration flows of young people is substantiated. The author presents a review of studies on educational migration and indicates the factors behind applicants’ choice of study location. The article dwells on the trends of interregional educational migration in the Volga Federal district, analyzes migration plans of high school seniors in Ulyanovsk region. The research bases on the methods of interdisciplinary literature analysis, sociological survey, method of expert assessments, and analysis of statistical data. The empirical base of the study became the results of a survey of 1010 high school seniors, 91 parents and 27 heads of educational institutions conducted in September-November 2018 in Ulyanovsk region. The proposed classification of the reasons for educational migration from the region and the reasons for staying in the region has a theoretical relevance. Based on the empirical data obtained, the ways of preventing educational migration from the region are suggested. In particular, it is revealed that the quality of education in regional universities is not a factor that significantly affects the choice of study location. To the greatest extent, the plans of school leavers are determined by the subjective perception of the socio-economic conditions of the region in which they would like to receive education. Since educational migration has objective and subjective reasons, the solution of this problem requires a set of economic, legal, advocacy tools. The article argues that there are two main forces in the region that can influence educational migration – these are the authorities and the territorial education system itself, the main structural elements of which are universities. In addition to the effective educational and scientific activities, universities need to conduct the targeted marketing policy, as well as to make efforts to promote their image and the image of the entire territorial education system.